Ungkapan Pamali Bagi Ibu Hamil: Studi kasus pada masyarakat Suku Sunda di Desa Ahua Watu - Ramlin; Ramli (FKIP, Universitas Lakidende Unaaha, 2022)
The culture of pamali exists in a community as a believe system of its members. This study aims at exploring the meaning of pamali expression for pregnant women firmly held by the Sundanese community in Ahua Watu village, Pondidaha sub-district. This qualitative research derived the data from three pregnant women as the informants using observation, interview, recording, transcription and note-taking techniquesS. The research found that the pamali expressions prohibiting the pregnant women from were: 1) eating using the lids of embe and plate, 2) hitting a person or animal by using a broom stick, 3) prohibition from firing wood in reverse direction, 4) stepping the chicken manure, as well as other livestock manure such as cow dung, buffalo, goats, and so on, 5) consuming sugarcane, 6) slaughtering and killing animals, 7) going out after sunset, 8) squeezing the laundry by trampling with feet, 9) hanging a towel or sarong on neck, 10) sewing anything, 11) using a necklace, 12) consuming any kind of jackfruit, 13) consuming shrimp and crab, 14) consuming bean sprouts, 15) consuming gourami fish, 16) putting stones into pockets and other places, 17) consuming wasps, 18) eating using a large plate, 19) being stingy for sharing something to others, 20) sitting in front of the door, 21) storing dirty water anywhere, 22) consuming pineapple, 23) scratching two parts of the body (stomach and buttock), and 24) burning all equipments for the baby to be born. These pamali expressions are intended for protecting the mother and the baby-to-be.